The importance of CD4 count, viral load and highly active antiretroviral therapy in HIV-associated thrombotic thrombocytopenic purpura (TTP). Issue 1 (1st November 2011) - Hill, Quentin A; Minton, Jane
Abstract : A case is reported of HIV-associated thrombotic thrombocytopenic purpura with normal CD4 count but high HIV viral load, developing neurological and cardiac complications up to 36 days after initiation of plasma exchange, but remitting within 18 days of the start of highly active antiretroviral therapy and steroids. In addition to plasma exchange, prompt initiation of highly active antiretroviral therapy in patients with HIV-associated thrombotic thrombocytopenic purpura may be justified despite a normal CD4 count.